Survey and Assessment of Willingness to Pay (WTP) for Reducing the Health and Environmental Risks of Vegetable Production Activities inBinh Chanh District, Ho Chi Minh City - Thi Anh Ngoc, Vu; Anh Hoa, Thai; Kim Thoa, Nguyen; Minh Ky, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2021)
The paper presents the current state of using pesticides and Willingness to Pay (WTP) to reduce vegetable producers’ health and environmental risks in Binh Chanh District, Ho Chi Minh City. This study used random sampling method by investigating 60 households (30 normal farm households and 30 VietGAP households). The main contents cover assessment on the impacts of using  pesticides, conducting WTP surveys to reduce health and environmental risks due to exposure to pesticides and analyzing marginal effects related to the Log - Lin regression model. Regarding the current, the normal vegetable producers tended to use more pesticides and exceed recommended doses compared to VietGAP group. The regression model explained 86,0 percent of the changes in farmers' WTP. The estimation results of the affecting factors to WTP showed that the variables such as agricultural promotion (X 3 ), income (X 4 ), amount of group I&II pesticides (X 5 ), the frequency of exposure of group I&II pesticides (X 7 ), and dummy variables GAP (GAP) were statistically significant (p<0,05). Therefore, the study proposed relevant solutions to reduce health and environmental risks in vegetable production for the safe use of pesticides.